Transcriptomics Reveals the Putative Mycoparasitic Strategy of the Mushroom Entoloma abortivum on Species of the Mushroom Genus Armillaria - Rachel A. Koch (American Society for Microbiology, 2021)

(untitled)
By studying fungi that parasitize other fungi, we can understand the basic biology of these unique interactions. Studies focused on the genetic mechanisms regulating mycoparasitism between host and parasite have thus far concentrated on a single fungal lineage within the Ascomycota.